Rheumatoid Arthritis Associated With Anti-Signal Recognition Particle Immune-Mediated Necrotizing Myopathy: A Case Report - Mohamed Reda Belkhribchia MD; Johannes Alexander Lobrinus MD; Lamyaa Semlil MD; Nicolas Chauveau MD; Abdelaziz Ajrinija MD; Kristof Egervari MD; Zine Elabidine Ennhaili MD (Journal of Investigative Medicine High Impact Case Reports, 2024)
Immune-mediated necrotizing myopathy (IMNM) is a rare subtype of idiopathic inflammatory myopathy that is characterized by severe subacute proximal weakness, myofiber necrosis, and significantly elevated serum creatine kinase. Anti-signal recognition particle (SRP) and anti-3-hydroxy-3-methylglutaryl-coenzyme-A reductase autoantibodies have been found in about two-thirds of patients with IMNM. This myopathy is usually idiopathic and there is a scarce literature concerning its association with connective tissue diseases. Herein, we report an unusual case of a young woman who presented with both rheumatoid arthritis and severe anti-SRP IMNM. Thankfully to a therapeutic protocol combining rituximab and cyclophosphamide, an important improvement was achieved, and notably no serious side effect was observed.